Courses

# -(−2) × (3 + 5) = ________a)-16b)-10c)10d)16Correct answer is option 'D'. Can you explain this answer? Related Test: Test: Integers - 2

## Class 7 Question

By Uma Shankar Singh · Jun 13, 2018 ·Class 7
Palak answered Jun 13, 2018
-(-2)Ã—(3+5) = 2Ã—8= 16

Rishabh Kumar Nayak answered Jun 04, 2018
16

Aryan Gupta. answered Jun 18, 2018
(-)Ã—(-) = +so answer is d.....

Vaishnavi answered Jun 22, 2018
-(-2)Ã—(3+5)=-(-2)Ã—8 {-*-}=+ 2Ã—8=16

Wahid Khan answered Nov 12, 2019
By applying BODMAS rule to the above equation

-(âˆ’2) Ã— (3 + 5) =( 2) x (8) = 16

Nitu Dutta answered 2 weeks ago
à§§à§¬

Shashwat Singh answered Jun 22, 2018
{-(-2)}Ã—(3+5) = {- (-2)}Ã—8 = 2Ã—8 = (16) That is option d

Sreyash Suyigya answered Jul 20, 2019
-(-2)Ã—(3+5)
=2Ã—(8)
=2Ã—8
=16 Ans..

Tanvi Mankotia answered 3 weeks ago
16 because -(-2) Ã—(3+5)

=+2Ã—(3+5)
=2Ã—8
=16

Pavithra Pravin answered Jun 22, 2018
It's bcoz.. -(-2) Ã— ( 3 + 5 ) = 2 Ã— 8 ( as, minus into minus is plus so.. -(-2) is +2 and (3 + 5) is 8 ) = 16 Hope this will help you:-)

Vimala Panga answered Jun 18, 2018
Hi

Gaurang Patel answered Feb 10, 2020
-- and -- makes positive . -- --2 = 2
3+5 Ã—2
8Ã—2
= 16

Abhimannu Kumar answered May 06, 2020
The answer will (16)

Anshagrahari0 answered Jun 13, 2018
Because - - = + then -(-2)=2 ONLY Ã—(3+5)=8 answer is 16

Option D

Karni Singh answered 4 weeks ago
-(-2)*(3+5) =2*8=16

Prakash Choubey answered May 08, 2020
Because it is clear that -(-2)=2

Kunal answered Feb 02, 2020
By applying BODMAS rule to the above equation
-(−2) × (3 + 5) =( 2) x (8) = 16

-Ã—-=+, 3+5=8 2Ã—8=16

Arul Murugan answered Jun 18, 2018
-Ã—- is + then 2Ã—3+5=2Ã—8=16

Deebyajyoti answered Jun 18, 2018
The answer is D means 16

Anna Joseph. answered Jun 18, 2018
When 2 --comes it is going to + so 2Ã—3+5=8 so,2Ã—8=16 so 16 is the answer...

Manpreet Kalra answered 3 days ago
-(-2)Ã—(5+3)=2Ã—8=16

Ayush Chauhan answered Jun 13, 2018
Correct answer is option d

Iqra Khan answered Sep 20, 2018
(-)(-)=+

D) 16

Dev Shah answered Jun 18, 2018
-(-2)Ã—3+5=2Ã—8=16

Ashmit Saxena answered Jun 23, 2018
=-(-2)*(+3+5) =-(-2)*8 ,because we solve bracet first =16 so the ans is -16

Bishal Kumar Gupta answered Jun 22, 2018
First= -Ã— -=+ So,+2Ã—[3+5]= 2Ã—8=16

Aman Panda answered Jun 22, 2018
16

Piyush Singh answered Sep 25, 2018
_16

Jayesh Kothariya answered Sep 26, 2018
D

Fortune Karanja answered May 06, 2020
By applying BODMAS RULE to the equation

Kaarthikha Shree answered Sep 19, 2018
3+5=8 8*-2=16

Sahil Dhiman answered Jun 22, 2018
-(-2)Ã—(3+5)=2Ã—8=16 therefore the answer is d

Rajesh Gupta answered Jun 22, 2018
16

Raju Kandharkar answered 2 weeks ago
16.

Amit Dhillon answered Jun 22, 2018
=-(-2)*(3+5) =_(-2)*8 =--=+therefore 2*8 =16. Is ans. Because - - =+

Satyam Bhardwaj answered Sep 20, 2018
In this question, , Before 2 1 negative is given out of the bracket and one is given in of the bracket. so meaning of bracket is multiply then -Ã—-= ..so then,, 2Ã—(3 5) so,3 5=8. then 2Ã—8 =16...

Soham Kulkarni answered Sep 25, 2018
Crroct and -16

Mehak Verma answered Sep 20, 2018
Because (-) =(-) =+ 2Ã—8=16

Shaiba Rahman answered Aug 28, 2018
The answer is 16

-(-2)* (3+5)2* 8
16

Simrati Lalwani answered Jul 21, 2019
= -(-2) Ã— (3+5)
= (-2) Ã— (3+5)
= (-2) Ã— 8
= -16
That is (a) part

-(-2)Ã—(3+5)=+2Ã—8=16
So correct answer is A ,not D

10

Rudhra Sree answered Jun 26, 2018
16

Arun Kumar answered Jun 18, 2018
A

Harish Raghuwanshi answered Aug 29, 2018
16

Vandna Dhamija answered Sep 03, 2018
16

Vivek Thapar answered Sep 20, 2018
-(-2)*(3+5)
- - = +
2*8
16

Aman Prabhakar answered Sep 19, 2018
16

Anant Jee answered Jun 23, 2018
16

Mohd answered Jun 22, 2018
A

Suzain Shamim answered Sep 26, 2018
16

Vandita Moolchandani answered Sep 19, 2018
I cannot understans this question

Joshua Aravind answered Jul 16, 2019
-(-2)*(3+5)=. -. and - join together means it becomes+ then +2*3+5 .

3+5 =8
then, +2*8=16
* this symbol is nothing but multiplication. my answer is 16

Saumya Singh answered Sep 03, 2018
-(-2) X (5+3)=+2X8......=16so that's why answer is 16

Cav Lc answered Sep 03, 2018
-(-2) = 2 3 + 5 = 8Therefore, -(-2) * (3 + 5) = 2 * 8 = 16

Sam Kashyap answered Aug 29, 2018
-(-2)Ã—(3+5) +2Ã—(3+5) 2Ã—8 16ans

Harendra Singh answered Sep 26, 2018
-and-=+-(-2) it mean +2after 2Ã—3+52Ã—8=16

Sagar Ahlawat answered Sep 20, 2018
We take -(-2)Ã—(3+5)=16 because -and -and -=+so we first multiply 2Ã—3=6 then 2Ã—5=10 and 10+6 =16 and -and - cut and formation of+ so answer 1

Ansh Singh answered 3 days ago
2*5+3=16

Varsha Jayesh Parmar answered Sep 01, 2018
(-) (-)=+ +2Ã—(3+5)= 16

Tanu Tanu answered Sep 01, 2018
16

Shivangi Tidke answered Sep 20, 2018
Becuse -(-2)will convert in to positive so equation is now 2 into (3 5) so we will get 8. so now we can directly multipy 2 into 8=16 so option is "d"

Manish Kumar answered Sep 26, 2018
16

Supriyanto Maftuh St answered Jun 18, 2018
A

-(-2)Ã—8. 2Ã—8=16. So option B) is right.

Mastermind Of All Subjec answered 2 weeks ago
The correct answer is 16 because -(-2)*(3+5) = 2*8 = 16